2020
DOI: 10.1016/j.brat.2019.103548
|View full text |Cite
|
Sign up to set email alerts
|

Family network satisfaction moderates treatment effects among homeless youth experiencing suicidal ideation

Abstract: Objective.-Limited research has evaluated the efficacy of suicide prevention interventions among homeless youth, especially considering how their connectedness with their family would impact treatment outcomes.Method.-Suicidal homeless youth (N = 150) between the ages of 18 to 24 years were recruited from a local drop-in center. Youth were randomly assigned to Cognitive Therapy for Suicide Prevention (CTSP) + Treatment as Usual (TAU) or Treatment as Usual alone. Youth reported their family network satisfaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(29 citation statements)
references
References 52 publications
3
24
2
Order By: Relevance
“…Three studies are reported in representing four papers ( Table 2 ). Slesnick et al [ 16 ] and Wu et al [ 36 ] are geographically located in the US and report outcomes following a randomized controlled trial. Lynn et al [ 37 ] study was also located in the US, and Adams et al [ 38 ] was based in Ireland.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Three studies are reported in representing four papers ( Table 2 ). Slesnick et al [ 16 ] and Wu et al [ 36 ] are geographically located in the US and report outcomes following a randomized controlled trial. Lynn et al [ 37 ] study was also located in the US, and Adams et al [ 38 ] was based in Ireland.…”
Section: Resultsmentioning
confidence: 99%
“…Lynn et al [ 37 ] study was also located in the US, and Adams et al [ 38 ] was based in Ireland. The study populations consist of adult participants and staff members [ 38 ], adolescents and their parents [ 37 ] and young adults aged 18 to 24 years [ 16 , 36 ]. All studies report randomized controlled trial methods, except for Adams et al [ 38 ] reporting a mixed-methods study ( Table 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A recently completed trial of CTSP builds the evidence-base for adaptations of effective interventions that can be delivered to address suicide risk among homeless youth. Among 18–24 year old homeless youth with suicidal ideation at high risk for suicide ( n = 150), suicidal ideation declined faster among youth randomized to CTSP relative to those in usual care [ 22 , 23 ]. Importantly, the trial of CTSP among homeless youth demonstrated effectiveness and was delivered at a homeless youth drop-in center by the center’s staff therapists.…”
Section: Introductionmentioning
confidence: 99%